A phase 1b randomized study of the safety and immunological responses to vaccination with H4:IC31, H56:IC31, and BCG revaccination in Mycobacterium tuberculosis-uninfected adolescents in Cape Town, South Africa. (April 2020) - Bekker, Linda-Gail; Dintwe, One; Fiore-Gartland, Andrew; Middelkoop, Keren; Hutter, Julia; Williams, Anthony; Randhawa, April K.; Ruhwald, Morten; Kromann, Ingrid; Andersen, Peter L.; DiazGranados, Carlos A.; Rutkowski, Kathryn T.; et al.
Abstract: Background: Tuberculosis (TB) remains the leading cause of infectious disease-related death. Recently, a trial of BCG revaccination and vaccination with H4:IC31, a recombinant protein vaccine, in South African adolescents (Aeras C-040-404) showed efficacy in preventing sustained QuantiFERON (QFT) conversion, a proxy for Mycobacterium tuberculosis ( M.tb ) infection. A phase 1b trial of 84 South African adolescents was conducted, concurrent with Aeras C-040-404, to assess the safety and immunogenicity of H4:IC31, H56:IC31 and BCG revaccination, and to identify and optimize immune assays for identification of candidate correlates of protection in efficacy trials. Methods: Two doses of H4:IC31 and H56:IC31 vaccines were administered intramuscularly (IM) 56 days apart, and a single dose of BCG (2–8 × 10 5 CFU) was administered intradermally (ID). T-cell and antibody responses were measured using intracellular cytokine staining and binding antibody assays, respectively. Binding antibodies and CD4+/CD8+ T-cell responses to H4- and H56-matched antigens were measured in samples from all participants. The study was designed to characterize safety and immunogenicity and was not powered for group comparisons. (Clinicaltrials.gov NCT02378207). Findings: In total, 481 adolescents (mean age 13·9 years) were screened; 84 were enrolled (54% female). The vaccines were generally safe and well-tolerated, with no reported severe adverse events related to the study vaccines. H4:IC31 and H56:IC31 elicited CD4+ T cells recognizing vaccine-matched antigens and H4- and H56-specific IgG binding antibodies. The highest vaccine-induced CD4+ T-cell response rates were for those recognizing Ag85B in the H4:IC31 and H56:IC31 vaccinated groups. BCG revaccination elicited robust, polyfunctional BCG-specific CD4+ T cells, with no increase in H4- or H56-specific IgG binding antibodies. There were few antigen-specific CD8+ T-cell responses detected in any group. Interpretation: BCG revaccination administered as a single dose ID and both H4:IC31 and H56:IC31 administered as 2 doses IM had acceptable safety profiles in healthy, QFT-negative, previously BCG-vaccinated adolescents. Characterization of the assays and the immunogenicity of these vaccines may help to identify valuable markers of protection for upcoming immune correlates analyses of C-040-404 and future TB vaccine efficacy trials. Funding: NIAID and Aeras.